Benthic Foraminifera as bio-indicators of anthropogenic impacts in coastal environments: Acqua dei Corsari area case study (Palermo, Italy). Issue 1 (15th April 2017) - Musco, Marianna; Cuttitta, Angela; Bicchi, Erica; Quinci, Enza Maria; Sprovieri, Mario; Tranchida, Giorgio; Giaramita, Luigi; Traina, Anna; Salvagio Manta, Daniela; Gherardi, Serena; Mercurio, Pietro; Siragusa, Angelo; et al.
Abstract: This study investigates living benthic foraminiferal assemblages as bio-indicators of anthropogenic activities in a coastal area within the Gulf of Palermo (Sicily, Italy), affected by industrial and urban activities, and evaluates the environmental quality through the calibration of a Tolerant Species index (%TSstd ). Sediments from 6 stations were sampled along a bathymetric transect from the coast to offshore. Sediment grain size, TOC, major, minor and trace elements and polycyclic aromatic hydrocarbons (PAHs) were compared to benthic foraminiferal assemblages and species at each station. Diversity and density of benthic foraminiferal assemblages were not affected by the presence of pollutants, while tolerant species increased with organic (TOC and PAHs) or chemical (As and Pb) concentrations. Moreover, the calibration of the %TSstd formula to > 125 μm foraminiferal assemblage, gives a detailed description of environmental quality along the transect, representing a good and sensitive tool to evaluate marine coastal environment. Highlights: Study of a coastal area affected by the presence of the sewage treatment plant Evaluation of natural and antropogenic impact on benthic foraminiferal assemblages Assessment of environmental quality through tolerant species (%TSstd ) m TOC influence on foraminiferal assemblages Benthic Foraminifera to evaluate the ecological quality for sewage treatment plant areas